Modelo de negocios para la creación de un establecimiento personalizado de perros calientes en el municipio de Guadalupe Huila (2021)
The objective of this project is to design and implement a personalized hot dog restaurant in the municipality of Guadalupe Huila, presenting a business opportunity based on an innovative fast food service. Where shareholders will be shown the opportunity to invest in a service that is increasingly influential in the food economy, with a focus on social impact, a financial analysis based on the continuous increase in the country's economy and the gastronomic field. Through an arduous investigation, it will be possible to evaluate the success of the management in order to reach the proposed objectives, in which they can be formalized taking into account the studies presented in the investigation, demonstrating the positive impact of managing the provision of an innovative service.